The academic-practitioner divide in intelligence studies - Arcos, Rubén 1977; Drumhiller, Nicole K. 1980; Phythian, Mark (Security and professional intelligence education series (SPIES), 2022)
"To a significant extent both the profession of intelligence and those delivering intelligence education share a common aim of developing intelligence as a discipline. However, this shared interest must also navigate the existence of an academic-practitioner divide. Such a divide is far from unique to intelligence - it exists in various forms across most professions - but it is distinctive in the field of intelligence because of the centrality of secrecy to the profession of intelligence and the way in which this constitutes a barrier to understanding and openly teaching about aspects of intelligence. How can co-operation in developing the profession and academic study be maximized when faced with this divide? How can and should this divide be navigated? The Academic-Practitioner Divide in Intelligence provides a range of international approaches to, and perspectives on, these crucial questions"--